P-type conductivity in Sn-doped Sb2Se3. (1st October 2022) - Hobson, Theodore D C; Shiel, Huw; Savory, Christopher N; Swallow, Jack E N; Jones, Leanne A H; Featherstone, Thomas J; Smiles, Matthew J; Thakur, Pardeep K; Lee, Tien-Lin; Das, Bhaskar; Leighton, Chris; Zoppi, Guillaume; et al.
Abstract: Antimony selenide (Sb2 Se3 ) is a promising absorber material for thin-film photovoltaics. However, certain areas of fundamental understanding of this material remain incomplete and this presents a barrier to further efficiency gains. In particular, recent studies have highlighted the role of majority carrier type and extrinsic doping in drastically changing the performance of high efficiency devices (Hobson et al 2020 Chem. Mater. 32 2621–30). Herein, Sn-doped Sb2 Se3 bulk crystals are shown to exhibit p-type conductivity using Hall effect and hot-probe measurements. The measured conductivities are higher than those achieved through native defects alone, but with a carrier density (up to 7.4 × 10 14 cm −3 ) several orders of magnitude smaller than the quantity of Sn included in the source material. Additionally, a combination of ultraviolet, x-ray and hard x-ray photoemission spectroscopies are employed to obtain a non-destructive depth profile of the valence band maximum, confirming p-type conductivity and indicating a majority carrier type inversion layer at the surface. Finally, these results are supported by density functional theory calculations of the defect formation energies in Sn-doped Sb2 Se3, showing a possible limit on the carrier concentration achievable with Sn as a dopant. This study sheds light on the effectiveness of Sn as a p-type dopant in Sb2 Se3 and highlights avenues for further optimisation of doped Sb2 Se3 for solar energy devices.